Single Chest Drain Practice Reduces Discharge Opioid Prescriptions in Thoracic Surgery - Zorrilla-Vaca, Andres; Feldman, Hope; Antonoff, Maria; Sepesi, Boris; Hofstetter, Wayne; Rajaram, Ravi; Swisher, Stephen; Mena, Gabriel; Vaporciya, Ara; Mehran, Reza; Rice, David (The Thoracic and Cardiovascular Surgeon, 2021)
Introduction Chest drains are placed following pulmonary resection to promote lung re-expansion. The superiority of two chest drains at preventing postoperative complications has not been established, and practice remains largely dictated by surgeon preference. We sought to compare patient outcomes based on number of chest drains used.Methods This is a retrospective analysis including patients undergoing lobectomies and segmentectomies between March 2016 and April 2020. Patients were categorized based on number of chest drains placed and were matched 1:1 using the nearest neighbor (greedy) technique. Our primary outcome was opioid prescriptions at discharge (in morphine equivalent daily dose [MEDD]). Associations were tested using multilevel mixed-effects regression to account for variability between surgeons.Results A total of 1,094 patients met inclusion criteria. Single chest drain was used in 922 patients, whereas 172 had two chest tubes. After matching, there were 111 patients in each group. In multilevel mixed-effects logistic regression, patients treated with a single chest drain received fewer opioid prescriptions (β: −194 MEDD, 95% confidence interval [CI]: −302 to −86 MEDD, p < 0.01), were more likely to be opioid-free at hospital discharge (odds ratio [OR] = 2.11, 95% CI: 1.08–4.12, p = 0.03), and had lower readmission rates within 30 days (OR = 0.33, 95% CI: 0.13–0.84, p = 0.02). Single chest drain practice did not affect the risk of pulmonary complications and there was no statistically significant difference in length of hospital stay (3 days [interquartile range: 2–5] vs. 4 days [3–6], p = 0.08).Conclusion Single chest drain practice in lobectomies and segmentectomies was associated with less opioid prescription requirement without any increase in complications.
Keywords: VATS; chest drain; outcomes